2023
DOI: 10.4097/kja.22718
|View full text |Cite
|
Sign up to set email alerts
|

Hemidiaphragmatic paralysis after costoclavicular approach versus other brachial plexus blocks in upper limb surgery: a meta-analysis

Abstract: Background: The costoclavicular brachial plexus block (CCB) is a recently established technique that uses the infraclavicular approach and is performed just below the clavicle. This meta-analysis aimed to determine whether CCB can reduce the incidence of hemidiaphragmatic paralysis (HDP), which is a major adverse event related to brachial plexus block (BPB), while yielding comparable block performance as other BPB techniques.Methods: We searched electronic databases to identify relevant studies that compared t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
1
1
0
Order By: Relevance
“…This randomized, controlled prospective study with a relatively large sample size reported that the motor blockade efficacy of the CCB and ISB were comparable, while complications such as hemidiaphragmatic paralysis were notably less frequent in the CCB group. This observation aligns with the results of a meta-analysis comparing the CCB with other brachial plexus blocks [ 3 ]. A recent report on a block that serves as an alternative to another plan block for analgesia during upper limb and shoulder surgeries is also available [ 4 ].…”
supporting
confidence: 90%
“…This randomized, controlled prospective study with a relatively large sample size reported that the motor blockade efficacy of the CCB and ISB were comparable, while complications such as hemidiaphragmatic paralysis were notably less frequent in the CCB group. This observation aligns with the results of a meta-analysis comparing the CCB with other brachial plexus blocks [ 3 ]. A recent report on a block that serves as an alternative to another plan block for analgesia during upper limb and shoulder surgeries is also available [ 4 ].…”
supporting
confidence: 90%
“…While it is true that CCB is a diaphragm-sparing technique when compared to other approaches performed above the clavicle [27], caution should be exercised when comparing studies due to the differences in the definition of HDP used in each study. Our findings appear to conflict with a prior study that reported no cases of HDP when utilizing CCB in shoulder surgery [4].…”
Section: Incomplete Analgesiamentioning
confidence: 99%